The impact of monetary policy and credit risk on bank credit behavior: An analysis of banks listed on the Indonesian stock exchange - Cep Jandi Anwar; Indra Suhendra; Saharuddin Didu; Anggi Sayektiyani; Lilis Nur Kholishoh (Cogent Economics & Finance, 2023)
The study investigates macroeconomic and bank-specific determinants of credit for commercial banks from 2010Q1-2022.Q4 in Indonesia. The banking credit is divided into an investment, working capital, and consumption credits. The study aims to address a gap in the literature since most prior studies are concentrated on developed markets. A system generalized method of moment (GMM) estimator is employed to investigate the impact of central bank rates and credit risk on credit. Dynamic-GMM estimations find that the central bank rate has a negative impact on the three types of credits. Meanwhile, non-performing loans positively impact investment and working capital credits but negatively affect consumption credit. The interaction between central bank rate and non-performing loans negatively impacts investment and working capital credits but positively affects consumption credit. This study provides managers and policymakers with timely information regarding bank credit drivers, encouraging management to take necessary measures, and policymakers may consider the importance of macroeconomic conditions while creating a bank lending policy. Similarly, it informs potential investors on how to evaluate the data when choosing a better investment option.
Keywords: E20; E44; E58; 330; Central bank rate; consumption credit; investment credit; non-performing loans; panel GMM; working capital credit